Concept of Islamic Education According to Buya Hamka - Eggi Mega Rahmawati; Retno Wahyuningsih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
According to Hamka, Islamic educational thinking is where parents' religious guidance towards children is: helping humans obtain a decent living, but more than that, with knowledge humans will be able to know their God, refine their morals, and always try to seek Allah's pleasure. Because, the aim of education is to serve and worship Allah. Therefore, educational materials must include the following three things: knowledge, charity, morals and justice. It can be said that according to Hamka, Islamic education is both about education, both in terms of urgency, meaning, material and purpose, it can be understood that Islamic education is an effort to guide and provide faith based on Islamic religious teachings for students so that later after completing their education they can understand and practice the Islamic religion.